Timber extraction and social organization in the Virola-Jatobá Sustainable Development Project, Anapu, Pará: Contrasting perceptions and discourses within an environmentally-sound land reform settlement - Assunção, Helder do Nascimento; Porro, Roberto (Sustainability in Debate, 2018)
Sustainable Development Project (PDS) is a land tenure modality aiming to reconcile agrarian reform and environmental conservation. Since the creation of Virola-Jatobá’s PDS (Anapu, PA), families struggle to consolidate their settlement. Timber extraction conducted between 2008 and 2012 through community partnership with a logging company has broadened local livelihoods’ perspectives. However, problems in activity implementation heightened associative disruption. In this article we analyzed settlers' perception regarding logging through forest management and benefits derived from logging as well as whether this perception was linked to household features. Discourses of selected settlers were compared according to lot accessibility, arrival time and participation in internal associations. The associative variable better distinguished perceptions regarding insertion of logging in local productive strategies. The achievement of socio-environmental goals foreseen in the PDS is thus conditioned to collective harmonic actions seeking compromises and a consolidated agenda for the benefit of the entire group.